Clinical and genetic spectrum in Chinese families with Fabry disease: a single‐centre case series. (26th October 2021) - Chen, Xin; Li, Hezhi; Liao, Hongtao; Zhan, Xianzhang; Zhong, Zhian; Zhang, Qianhuan; Liu, Lie; Liang, Yuanhong; Deng, Hai; Fang, Xianhong; Xue, Yumei; Wu, Shulin; et al.
Abstract: Aims: Fabry disease (FD) is an X‐linked genetic disease caused by mutations in the GLA gene that leads to deficient activity of lysosomal enzymes, accumulation of globotriaosylceramide in multi‐organ systems, and variant clinical manifestations. We aimed to detail the clinical and genetic spectrum of FD in Chinese families. Methods and results: Five male probands with unexplained left ventricular hypertrophy and their family members were investigated. Genetic screening was available in 11 subjects of the 5 families, 10 of whom proved to be carriers of either GLA gene mutation, including 3 previous reported missense mutations (c.128G > A, c.811G > A, c.950T > C), 1 novel missense mutation (c.37G > C), and 1 novel deletion mutation (c.1241delT). A total of 17 patients were definitely or possibly diagnosed of FD, given their clinical manifestations and hereditary nature of FD. Echocardiography demonstrated normal cardiac structure and function in six female patients. Electrocardiographic pre‐excitation occurred in 80% (4/5) of men and 16.7% (1/6) of women. Six patients (6/14, 42.9%) had chronic kidney disease with decreased renal function and all were male (6/7, 85.7%). Six patients presented with acroparesthesia, hypohidrosis, or both. Three female patients and two male patients experienced sudden death, and one male patient with the mutation (c.128G > A) died of progressive heart failure, between 41 and 66 years of age. Conclusions: We reported five unrelated families of FD with different GLA mutations. Clinical manifestations were highly heterogeneous between male and female patients even within the same family. Female patients showed relatively low risks of structural heart disease and renal insufficiency. However, the long‐term outcomes might be adverse in both sexes. Our study underlines the importance of molecular screening of the GLA gene for early identification and clinical decision making in patients with FD.